Web use and offshoring - Aoife Hanley; Ingrid Ott (Kiel Institute for the World Economy (IfW), 2009)
Formulating a model which summarises transportation costs, uncertainty and price, we describe how a switch to ICT procurement can impact more readily procured services rather than materials. Uncertainty represents a catch-all factor describing the dovetailing of operations between two neither culturally nor geographically proximate, independent firms. Using a 3-year panel, we find that ICT 'switchers' report increases in services offshored by between 1.9 and 1.6 percent. Uniquely, we also report a 2-3 percent reduction in the level of materials offshoring following a switch to internet procurement.
Keywords: 330; Offshoring; heterogeneous inputs; uncertainty; price; transportation costs; Beschaffung; Vorprodukt; E-Business; Internet; Materialwirtschaft; Offshoring; Transportkosten; Entscheidung bei Unsicherheit; Preis; Theorie; Irland